Characterization and Effective Dose of Gross Alpha and Gross Beta Activities in Particulate Matters (PM2.5, PM10, SPM) in India - Yadav A.K. (My University, 2025)
A radiometric composition of airborne particles sample, collected twice a week for two consecutive years at Singrauli coalfield, India, is analyzed. The average ratio between gross alpha and gross beta in the particulate matter was observed 0.63 (PM2.5), 0.73 (PM10) and 0.91 (Suspended particulate matter). The seasonal variation of gross alpha radioactivity shows a minimum in the rainy and a maximum in the winter. These results are relevant to understanding the meteorological factors affecting alpha and beta activity concentrations in this area. The correlation between gross alpha and gross beta activities suggests a similar source. Minimum and maximum individual effective annual dose of gross alpha and gross beta due to particulate matters were caused by 137Cs and 232Th, respectively. In this study, the detailed aspects of activity have been investigated and discussed in the study area. © 2022, The Author(s) under exclusive licence to Institute of Earth Environment, Chinese Academy Sciences.